1999
DOI: 10.1006/jcta.1998.2891
|View full text |Cite
|
Sign up to set email alerts
|

Eulerian 2-Strata Spaces

Abstract: In (B. F. Chen and M. Yan, 1998, Eulerian stratification of polyhedra, Adv. in Appl. Math. 21, 22 57), we introduced the notion of Eulerian stratified spaces. In this paper, we study in detail the topological and combinatorial properties of Eulerian 2-strata spaces, as the first step toward a deeper understanding of more strata cases. We show that Eulerian 2-strata spaces have similar topological structure as topological 2-strata spaces. Moreover, we find all the linear conditions on f-vectors over arbitrary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Following Klee's work, the authors 7,8 showed that the notion of Eulerian manifolds is actually independent of triangulations. Furthermore, Ž we studied the more general two-strata spaces including manifolds with .…”
mentioning
confidence: 99%
“…Following Klee's work, the authors 7,8 showed that the notion of Eulerian manifolds is actually independent of triangulations. Furthermore, Ž we studied the more general two-strata spaces including manifolds with .…”
mentioning
confidence: 99%